Improvement of the technique of determination of electric energy losses in 10(6) kV networks by means of fuzzy sets theory - Kutin, V. M.; Kulyk, V. V.; Pyskliarov, D. S. (Visnyk of Vinnytsia Politechnical Institute, 2010)
New approach to modeling of the coefficient of group loading form is offered by means of theory of fuzzy sets for the tasks of electric energy losses calculation in distributive networks.